Videolaryngoscopy versus direct laryngoscopy in without muscle relaxation intubation conditions in tympanomastoidectomy: A randomized, prospective clinical study (Annals of Medical Research, 2021)
None
Keywords: s: Intubation Without Muscle Relaxants; Laryngoscopy; Hemodynamic Responses; Videolaryngoscopy.